Clinical profile and changes in laboratory parameters among dengue patients at tertiary care hospital: an observational study - Pande, Pankaj Ashok; Jogdande, Amit Jagdish (International Journal Of Community Medicine And Public Health, 2019)
Background: Globally the incidence of dengue has increased in the past three decades. It is predominantly found in the urban and semi-urban area however now it is spreading in rural areas also. In India the incidence of dengue has increased due to rapid urbanization, lifestyle changes and improper water storage practices. Hence this study was planned to study the clinical and laboratory profile of dengue patient as the number of dengue patients is on rise every year and there is varied presentation of clinical features in different parts of India. Methods: This observational study was carried out in tertiary care hospital. Confirmed cases of Dengue were included in the study. There cases were observed seven days. During this period their clinical and biochemical profile was recorded in pre structured and pre tested proforma. Data was compiled and analyzed by MS-Office (Excel) and SPSS-21. Results: In this study total 129 patients were enrolled. Out of total 91 were males and 38 were females. Laboratory profile of dengue patients suggested steep decline in total leucocytes count and platelet during first five days but started to increase by seventh day but platelets have not reached to its original normal value while TLC reverted to normal range. Fever and headache were most common symptom in our study. Conclusions: Clinical and laboratory profile of dengue patient changes with every new epidemic and different region in India. Clinical features like organomegaly are more common in paediatrics age group than adults.